Value Co-Creation in AI-Based Technology Adoption: From Service-Dominant Logic to Intelligent Digital Ecosystems - Agung Wijoyo; Sri Suwarsi; Tasya Aspiranti (Jurnal Manajemen Bisnis dan Kesehatan, 2026)
The rapid expansion of AI-enabled digital ecosystems has shifted technology adoption from purely functional evaluation to interactive, personalized, and co-created user experiences. However, existing studies remain largely rooted in cognitive perspectives and have not fully addressed the roles of va lue co-creation, perceived value, psychological ownership, and relational engagement. This study conducts a systematic literature review with thematic analysis to examine the evolution of value co-creation from Service-Dominant Logic to intelligent digital ecosystems and its implications for AI-based technology adoption. Findings reveal that adoption increasingly occurs through ecosystem interaction, participatory engagement, and personalization rather than solely functional assessment. Key mechanisms shaping adoption intention include perceived value, psychological ownership, ecosystem trust, and relational engagement. The study contributes by extending traditional technology acceptance models toward an ecosystem-based perspective grounded in value co-creation and intelligent digital interaction. Practically, it offers insights for organizations and platform providers in designing AI-enabled ecosystems that enhance engagement, trust, and sustainable adoption.